Análisis de tendencias temporo espaciales y factoriales de COVID – 19, en la provincia de El oro, del periodo 2020-2022 - Ortega Riofrio, Carla Mishell (2024)
Coronavirus disease 2019 (COVID – 19) is caused by severe acute respiratory syndrome virus-2 (SARS–CoV–2), which was declared a pandemic in March 2020, it is highly contagious and is transmitted rapidly from person to person through coughing or respiratory secretions and by close contacts. In Ecuador until January 2022, 593,664 cases of infection have been confirmed, a daily increase of 3,320. The course of the disease is variable and ranges from asymptomatic infection to severe pneumonia. The present research aimed to determine the epidemiological behavior of COVID-19 through characterization according to sex, age, canton of contagion and the climatic seasons, with the purpose to set out an educational and/or preventive strategy focused on the spread of the disease. An analytical study with a mixed approach was conducted whose study population was 48528 cases obtained from the databases of the epidemiological gazettes of the National University of Loja. The findings determined that: the age group where the cases predominated was that of 20 to 49 years with 61%, in women there is the highest number of cases with 50.8% and the most affected canton was Machala representing 52.3% of cases in the province; the proportional trends showed that there are more cases in the rainy season (57.4%) in relation to the dry season (42.6%), in the same way in the warm temperature (61.3%) in relation to the cold temperature (38.7%). Finally, a digital broadcast video was made and shared among the population that embraced the main definitions of the disease and the different community prevention measures